Determinan Persepsi Etis Mahasiswa Akuntansi - Tri Agustina; Amir Hidayatulloh (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2023)
The purpose of this study is to analyze the determinants of accounting students' ethical perceptions. The population in this study were students of Ahmad Dahlan University. The sample in this study were accounting at Ahmad Dahlan University. The sampling techniques in this study used purposive sampling, with criteria (1) Ahmad Dahlan University accounting students, and (2) taking business ethics, Islamic studies, and certification course. Respondents in this study were 130 respondents. Data analysis techniques in this study used multiple linear regression analysis with the help SPSS tools. This study found that ethical perceptions of accounting students were influenced by intrinsic religiosity and love of money. However, extrinsic religiosity and socioeconomic status do not affect the ethical perceptions of accounting students